The Synthesis of Peculiar Structure of Springlike Multiwall Carbon Nanofibers/Nanotubes via Mechanothermal Method. (13th June 2012) - Manafi, Sahebali; Rahimipour, Mohammad Reza; Mobasherpour, Iman; Soltanmoradi, Atefeh
Abstract : Mechanothermal (MT) method is one of the methods used for large-scale production of carbon nanotubes/nanofibers. The different peculiar morphologies of carbon allotropes are introduced with an extraordinary structure for the first time by MT method. In this paper, the influence of milling time and annealing temperature on the crystallinity and morphology of the synthesized nanopowders was investigated. Surprisingly, in this investigation, we report the synthesis of springlike multiwalled carbon nanofibers (S-MWCNFs) by a two-step annealing of milled graphite in an Ar atmosphere. On the other hand, the MT method could be used for the preparation of suitable structures with applications in nanocomposite materials, which is an important task in the era of nanotechnology.